2017
DOI: 10.1515/aiht-2017-68-2905
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene restores trace element levels in ochratoxin A-treated rats

Abstract: This study was designed to investigate the in vivo effects of ochratoxin A (OTA) and/or lycopene on the levels of selenium, zinc, and copper in the liver, kidneys, and testes of male Sprague-Dawley rats. The rats were treated with OTA (0.5 mg kg-1 day-1) and/or lycopene (5 mg kg-1 day-1) by gavage for 7 or 14 days. Trace element levels were measured by atomic absorption spectrometry. OTA significantly lowered selenium (20 % in the liver, 17 % in the kidney, and 40 % in the testis), zinc (24 % in the liver, 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Palabiyik et al reported a significant decrease in selenium, zinc, and copper levels in OTA-treated rats. The addition of lycopene did not affect the liver zinc level, whereas it markedly increased selenium and copper compared to the group treated with OTA only [ 140 ]. While OTA increased the number of apoptotic hepatocytes in mice to 97.20 ± 17.09, lycopene could reduce their number to 8.80 ± 5.02 [ 121 ].…”
Section: Preventionmentioning
confidence: 99%
“…Palabiyik et al reported a significant decrease in selenium, zinc, and copper levels in OTA-treated rats. The addition of lycopene did not affect the liver zinc level, whereas it markedly increased selenium and copper compared to the group treated with OTA only [ 140 ]. While OTA increased the number of apoptotic hepatocytes in mice to 97.20 ± 17.09, lycopene could reduce their number to 8.80 ± 5.02 [ 121 ].…”
Section: Preventionmentioning
confidence: 99%
“…Trace elements are components of intracellular antioxidants and can maintain cellular homeostasis. Lycopene restored OTA inhibition of selenium, zinc, and copper in the kidney, liver, and testis of rats [ 107 ]. In addition to being a component of many important enzymes, Zinc can also regulate the antioxidant gene expression.…”
Section: Preventionmentioning
confidence: 99%